Activities Oriented to Preparing Children with Disabilities for Preschool Inclusion - Serhat Odluyurt (Elementary Education Online, 2023)
When we look at the studies in support of preschool inclusion methods, we can see that the placement of young children with disabilities in an inclusive environment is advantageous. In methods oriented towards the inclusion of children in preschool, developing preparatory skills for inclusion is highly important. Preparatory skills for inclusion are mainly considered to be social-emotional skills, however they also include academic skills. For any inclusion effort to be successful, the associated preparatory skills must be determined and taught to children. Lack of inclusion preparatory skills in children of preschool age with disabilities when they are just about to transition into this environment will make it difficult for them to harmonize within an environment conducive to inclusion. Therefore these skills are required to be taught prior to the transition into the inclusive environment, but also reinforced during the process. This review study aims to introduce some of the preparatory skills for inclusion in the preschool period, as well as to provide information pertaining to the educational processes.